A structured-light 3D sensor-based shape measurement method for casting allowance evaluation - Luo, Hua; Zhang, Ke; Li, Ruifeng; Xia, Yu; Liang, Peidong (Frontiers in Physics, 2022)
The evaluation of casting allowance currently relies on manual operation, which is time-consuming and unstable. The structured-light three-dimensional (3D) sensor-based 3D shape measurement technology is credited with non-contact, high accuracy, and fast measuring speed, which provides the complete 3D shape of casting for accurate allowance evaluation. However, measuring a complex shape casting still requires a large number of manual operations including attaching marks, planning measurement process and data processing, etc. To solve these problems, a robot-driven structured-light 3D sensor-based measurement method is proposed, with a six-degree of freedom (6-DOF) industrial robot and a turntable to control the structured-light 3D measurement sensor, to transform the 3D results from different measuring viewpoints into a coherent coordinate system to form a complete 3D shape of the casting. Then, the mechanical processing allowance will be calculated by comparing the 3D measurement result and the standard CAD model automatically. The experiment results show that the proposed method is accurate and efficient, the casting allowance evaluation time is about ten times faster than that of manual operation. Moreover, the proposed method would provide valuable experience for other industrial applications.